The Impact Of A Nature-Based Environmental Education Programme: The Importance Of Environmental Knowledge And The Connection To Nature In Fostering Ecological Behaviour And Attitudes In Children - ZHENG CHUNYAN; NIDHI AGARWAL; AMINUL ISLAM (Revista Electronica de Veterinaria, 2024)
The available evidence on the influence of nature-based training on pro-environmentalism is equivocal, mostly due to the limited number of controlled studies undertaken on this subject. This complicates the ability to establish causal relationships and provide guidance for treatments. The researchers provide the findings of an experiment that examined the impact of a "nature-based environmental education (NBEE)" programme on children’s environmental attitudes (EA) & behaviours (EB) within their school curriculum. The children who took part in the project but traditionally got their education were used as the control group for the project. Spain has a total of seven elementary schools that participated in the scheme. Each school randomly assigned courses to either the NBEE curriculum or the "environmental education (EE)" programme, which was taught using traditional teaching methods. Based on our study’s results, the group that took NBEE saw a much higher increase in children’s EA compared to the group which received the control. Over time, the occurrence of EB in both groups of children remained rather constant on average. Based on our findings, academics highly advocate for the increased use of nature-based pedagogy in formal education to enhance children’s environmental attitudes.